2019
DOI: 10.1007/s00431-019-03440-6
|View full text |Cite
|
Sign up to set email alerts
|

Neonates living with enterostomy following necrotising enterocolitis are at high risk of becoming severely underweight

Abstract: Necrotising enterocolitis (NEC) is often managed with a temporary enterostomy. Neonates with enterostomy are at risk of growth retardation during critical neurodevelopment. We examined their growth using z-score. We identified all patients with enterostomy from NEC in two neonatal surgical units (NSU) during January 2012–December 2016. Weight-for-age z-score was calculated at birth, stoma formation and closure, noting severely underweight as z < − 3. We compared those kept in NSU until stoma closure with those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…[15,16] It is reported that in the presence of a stoma, up to 90% of the young children are declining on the growth chart, which is why some advocate early stoma closure. [17][18][19][20] This opinion is supported by the finding that most young children thrive after stoma closure, irrespective of morbidity, weight, or underlying pathology. [17] Considering the increased risk of malnutrition due to stoma morbidity and its impact on growth, it is interesting to see that weight at stoma closure and days until stoma closure were not significantly associated with morbidity following closure in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…[15,16] It is reported that in the presence of a stoma, up to 90% of the young children are declining on the growth chart, which is why some advocate early stoma closure. [17][18][19][20] This opinion is supported by the finding that most young children thrive after stoma closure, irrespective of morbidity, weight, or underlying pathology. [17] Considering the increased risk of malnutrition due to stoma morbidity and its impact on growth, it is interesting to see that weight at stoma closure and days until stoma closure were not significantly associated with morbidity following closure in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Neonate enterostomy is a common surgical method for treating acute and severe neonatal intestinal diseases [1]. It refers to a surgical opening into the intestine through the abdominal wall, creating a temporary arti cial anus to treat acute abdomen caused by neonatal necrotising enterocolitis, intestinal perforation, intestinal necrosis, intestinal atresia, poor intestinal rotation, intestinal volvulus, and anal atresia [2].…”
Section: Introductionmentioning
confidence: 99%
“…Stoma formation may involve complications associated with poor weight gain and electrolyte imbalance due to high intestinal output, stenosis, prolapse, stula formation, and excoriation of the surrounding skin. The metabolic or functional problems may, in some cases, demand surgical intervention before the planned stoma reversal, which may further increase the risk of complications (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Preoperative and operative characteristics are shown in Table2. After the surgery, initiation of enteral nutrition was possible after a median of 7.4 (range, 3-13) days in ELBW group and 5.7 (range,[3][4][5][6][7][8][9][10][11] days in VLBW group (p > 0.999). .669-77.09]; p 0.0001).…”
mentioning
confidence: 99%